2016
DOI: 10.15451/ec2016-8-5.6-1-17
|View full text |Cite
|
Sign up to set email alerts
|

Homegardens in a micro-regional scale: contributions to agrobiodiversity conservation in an urban-rural context

Abstract: Homegardens are conservation units for native plants and reservoirs of exotic species from different origins. We analysed the species composition and diversity of edible plants on three groups of homegardens in a gradient from urban to rural situations, but under the same historical and cultural contexts, and verified how these homegardens can favour the conservation of plants from different origins. The size of each homegarden was measured and complete inventories were carried out to assess the total edible p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 22 publications
1
19
0
8
Order By: Relevance
“…It was recorded that species of Myrtaceae family in particular (almost all native) are well represented and their presence, management and local importance may be the starting point of in situ conservation plans of species of the Atlantic Forest. The registration of various species of the family Myrtaceae in orchards has already been described for the same phytogeographic region by Peroni et al (2016) and their role in local conservation was also highlighted by these authors. The fruits of the Myrtaceae family are appreciated for direct consumption by local people of Iguazú.…”
Section: Discussionmentioning
confidence: 75%
“…It was recorded that species of Myrtaceae family in particular (almost all native) are well represented and their presence, management and local importance may be the starting point of in situ conservation plans of species of the Atlantic Forest. The registration of various species of the family Myrtaceae in orchards has already been described for the same phytogeographic region by Peroni et al (2016) and their role in local conservation was also highlighted by these authors. The fruits of the Myrtaceae family are appreciated for direct consumption by local people of Iguazú.…”
Section: Discussionmentioning
confidence: 75%
“…Common intrinsic factors are, for example, the size of the garden, its age, and its proximity to the dwelling, among others (Blanckaert et al 2004 ; Coomes and Ban 2004 ; Sander and Vandebroek 2016 ). On the other hand, research indicates that factors extrinsic to the garden, such as distance to urban centers, kinship, size of family groups, forms of management, and networks of exchange, may explain the species richness and diversity of home gardens (Díaz-Reviriego et al 2016 ; Ellen and Platten 2011 ; Lamont et al 1999 ; Peroni et al 2016 ; Sander and Vandebroek 2016 ). For example, studies have shown that peri-urban and urban home gardens may host a greater diversity of species than those situated in remote places.…”
Section: Introductionmentioning
confidence: 99%
“…Home gardens, for example, survived and evolved over centuries of biocultural transformations as one of the oldest systems of land use (Nair & Kumar 2006). Green lands and home gardens in urbanized areas promote diversity and food security, allow for adaptation to climate change, improve life quality and wellbeing and can also increase the connectivity between urbanized landscapes and remnant forest areas (Galhena et al 2013;Larios et al 2013;Mattsson et al 2013;Capaldi et al 2014;Peroni et al 2016;Ávila et al 2017;Shackleton et al 2017).…”
Section: Ethnobotany and Urbanization: How Do We Understand Pbks In Cmentioning
confidence: 99%